Organoleptic Characteristics of Dry Noodle Products from Yellow Sweet Potato (Ipomoea batatas): Study on Adding Eggs and CMC - Mulyadi, Arie Febrianto; Wijana, Susinggih; Dewi, Ika Atsari; Putri, Widelia Ika (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
In this research dried noodles making from sweet potato flour were carried out. Sweet potato varieties that used are Ace with yellow roots. The making of dry noodles from sweet potato flour required modification of the process because flour does not contain gluten. This study using some modifications in addition of eggs and Carboxy Methyl Cellulose (CMC). The aim of this study is to obtain the concentration of the addition of egg and CMC to produce dried noodles from sweet potato flour with the best quality of organoleptic. The experimental design was used a Randomized Block Design (RBD) is arranged with 2 factors. The first factor is the type of the addition of eggs which consists of three levels, namely 0%, 10%, and 20%. The second factor is the concentration of CMC consists of three levels, namely 0%, 1%, and 2%. Observational studies include observations organoleptic dry noodles with hedonic scale and the best treatment will be tested n physical quality. The results showed that the addition of different concentrations of CMC and eggs significantly different with a sense of liking for sweet potato dried noodles, while preference for color, aroma, and texture of sweet potato dry noodles were not significantly different. The best results for the organoleptic quality using CMC addition of 1% and 20% addition of eggs. The best organoleptic quality parameters at each of the color 4.2 (like slightly), the aroma of 4.4 (like slightly), sense of 5.4 (like slightly) and for texture by 5 (like slightly). Dried sweet potato noodles best treatment results have physical quality of cooking loss 17.48%, 54.80% swelling index, hydration of 66.42%, 1.58 ratio developments, water content 8.06% and a yield of 53%.Keywords: CMC, dry noodles, eggs, sweet potatoes, organoleptic